2008
DOI: 10.1534/genetics.107.085324
|View full text |Cite
|
Sign up to set email alerts
|

Visual Mutations Reveal Opposing Effects of Illumination on Arousal in Drosophila

Abstract: The effect of illumination on alertness can be assessed by comparing the efficacy of an anesthetic under light vs. dark conditions. Results from such tests on wild-type flies and visual mutants demonstrate that, surprisingly, light has both positive and negative influences on arousal. These dual effects may explain aspects of the fly's daily activity and have potential clinical implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…In the absence of anesthetic, no mutant line performs worse than control, so the poor performance of the JC lines in the presence of anesthetic does not appear to be due to weakened baseline locomotion. Note that the values for the inaF mutant confirm our previous observation that the relative resistance of this strain to halothane is dependent on ambient lighting (Cheng and Nash, 2008). See Methods for a description of the countercurrent test, the formulas used to calculate Pt and its confidence limits, and the basis for assignment of significant differences…”
Section: Figures and Tablessupporting
confidence: 87%
See 2 more Smart Citations
“…In the absence of anesthetic, no mutant line performs worse than control, so the poor performance of the JC lines in the presence of anesthetic does not appear to be due to weakened baseline locomotion. Note that the values for the inaF mutant confirm our previous observation that the relative resistance of this strain to halothane is dependent on ambient lighting (Cheng and Nash, 2008). See Methods for a description of the countercurrent test, the formulas used to calculate Pt and its confidence limits, and the basis for assignment of significant differences…”
Section: Figures and Tablessupporting
confidence: 87%
“…In recent work, we have concluded that ambient illumination has both positive and negative effects on arousal, and mutations can influence halothane sensitivity by changing the balance between these effects (Cheng and Nash, 2008). The most dramatic example of this phenomenon involved a null allele of inaF , the gene mutated in line JC09 (Cheng and Nash, 2007); in this case the mutant phenotype disappeared when the line was tested in the dark (Cheng and Nash, 2008). To see if this phenomenon was common in our mutant collection, Canton-S and the mutant lines JC02, JC05, JC07, JC11, and JC13 were tested both in ambient light and in the dark for climbing ability in the presence of a modest concentration of halothane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we concluded that in daylight w males are dazzled by the over-flow of light and that over-excitation of the photoreceptors suppresses their sexual arousal. In this context, it is remarkable that the sensitivity to the anesthetic halothane of w 1118 flies is increased in ambient light as compared to darkness, which suggests that light over-excitation affects the general state of arousal of w flies in daylight [31].…”
Section: Discussionmentioning
confidence: 99%
“…The second aim was to provide the tested lines with a wild-type copy of the white ( w ) gene, since the DrosDel parental and deletion lines all bear an allele of this gene ( w 1118 ) that is known to alter anesthetic sensitivity. 11,12 The final aim was to enable the possibility of finding genes that have a specific interaction with na . When homozygous, mutations in this gene confer strong effects on anesthesia sensitivity, but heterozygotes are indistinguishable from wild-type.…”
Section: Methodsmentioning
confidence: 99%